Comparison of clinical safety and feasibility between reduced-port laparoscopic radical gastrectomy and conventional laparoscopic radical gastrectomy: A retrospective study - Wang, Liang; Deng, Yingfang; Yan, Su; Ma, Xinfu; Wang, Cheng; Miao, Wei; Chen, Xiaoqian (Frontiers in Surgery, 2022)
Traditional open gastric cancer surgery has evolved from porous to reduced-hole, single-hole, or even natural cavity surgery to laparoscopic surgery, due to the continuous development of minimally invasive concepts and medical technologies, as well as awareness for the concept of rapid recovery. Conventional laparoscopic radical gastrectomy is quite mature in age at the moment, but how to progress to minimally invasive surgery without increasing the difficulty of surgery while ensuring clinical safety and feasibility is worth further investigation. Therefore, the clinical safety and feasibility of reduced port laparoscopic radical gastrectomy were assessed in this study.